2017
DOI: 10.1098/rstb.2016.0271
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus-associated lymphomas

Abstract: Epstein–Barr virus (EBV), originally discovered through its association with Burkitt lymphoma, is now aetiologically linked to a remarkably wide range of lymphoproliferative lesions and malignant lymphomas of B-, T- and NK-cell origin. Some occur as rare accidents of virus persistence in the B lymphoid system, while others arise as a result of viral entry into unnatural target cells. The early finding that EBV is a potent B-cell growth transforming agent hinted at a simple oncogenic mechanism by which this vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
305
1
23

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(357 citation statements)
references
References 148 publications
4
305
1
23
Order By: Relevance
“…12,13 It is postulated that all these factors contribute to a tolerogenic environment that promotes tumour immune escape, 14 much as iatrogenic immunosuppression does in EBV -pos post-transplant lymphoproliferative disorders. [15][16][17][18] Interestingly, we have previously shown that the T-cell receptor repertoire is a key determinant of the TME and is associated with outcome. 19 Furthermore, substantially higher clonal T-cell responses were observed in EBV -pos vs EBV -neg DLBCL.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 It is postulated that all these factors contribute to a tolerogenic environment that promotes tumour immune escape, 14 much as iatrogenic immunosuppression does in EBV -pos post-transplant lymphoproliferative disorders. [15][16][17][18] Interestingly, we have previously shown that the T-cell receptor repertoire is a key determinant of the TME and is associated with outcome. 19 Furthermore, substantially higher clonal T-cell responses were observed in EBV -pos vs EBV -neg DLBCL.…”
Section: Introductionmentioning
confidence: 99%
“…In ENKL, one of the main oncogenic driver, NF-kB, is driven by the EBV protein LMP1. LMP1 and NF-kB activate a series of genes that lead to the production of Th1 cytokines TNF-α and IFN-γ(34, 41). Moreover, in ENKL EBV infection promotes the upregulation on infected lymphoma cells of the PD-L1.…”
Section: Immune System In T Cell Neoplasms – Rationale For Immunotherapymentioning
confidence: 99%
“…Moreover, in ENKL EBV infection promotes the upregulation on infected lymphoma cells of the PD-L1. Binding of PD-L1 on lymphoma cells by PD1 on effector T cells suppresses T cell toxicity, allowing ENKL to escape this regulation(34, 41). This might explain the good activity of checkpoint inhibitors in ENKL.…”
Section: Immune System In T Cell Neoplasms – Rationale For Immunotherapymentioning
confidence: 99%
“…Epstein-Barr virus (EBV) infects nearly 95% of adults worldwide. The virus primarily causes infectious mononucleosis (IM) in adolescents, is closely associated with lymphoproliferative disease in immunocompromised individuals, and is linked to cancers including Burkitt lymphomas (BL), diffuse large B cell lymphomas (DLBCL), and nasopharyngeal carcinoma (1, 2). BL is a common childhood cancer in Africa, and >80% of cases are EBV positive (3).…”
Section: Introductionmentioning
confidence: 99%
“…BL is a common childhood cancer in Africa, and >80% of cases are EBV positive (3). As a germinal-center (GC) derived cancer, BL cells exhibit a centroblast-like phenotype (2, 4), maintained in part from activated c-myc oncogene expression (5), and have a molecular profile akin to GC dark zone proliferative B cells (6).…”
Section: Introductionmentioning
confidence: 99%